Chaotropic effects on 2,4,6-trinitrotoluene uptake by wheat (Triticum aestivum) - Datta, Rupali K.; Sarkar, Dibyendu; Shakya, Kabindra Man; Pachanoor, Devanand; Das, Padmini K.; Makris, Konstantinos C. (My University, 2007)
Previous research in our laboratory investigated the effectiveness of a common agrochemical, urea used as a chaotropic agent to facilitate 2,4,6-trinitrotoluene (TNT) removal by vetiver grass (Vetiveria zizanioides L.). Chaotropic agents disrupt water structure, increasing solubilization of hydrophobic compounds (TNT), and enhancing plant TNT uptake. Our findings showed that urea significantly enhanced TNT uptake kinetics by vetiver. We hypothesized that the beneficial effect of urea on the overall TNT uptake by vetiver grass was not plant-specific. We explored this hypothesis by testing the ability of wheat (Triticum aestivum L.) in removing TNT from aqueous media in the presence of urea. Results showed that untreated (no urea) wheat exhibited a slow, kinetically limited TNT uptake that was nearly half of the urea-treated wheat TNT capacity (250 mg kg-1). Chaotropic effects of urea were illustrated by the significant (P < 0.001) increase in the TNT second-order reaction rate constants over those of the untreated (no urea) controls. Plant TNT speciation showed that TNT and several of its metabolites were detected in both root and shoot compartments of the plant, allowing for 110 and 36% recovery for the untreated and 0.1% urea treated plants. The lower % recovery of the urea-treated plants was attributed to a number of unknown polar TNT metabolites.
Keywords: Chaotropic; Metabolites; Phytoremediation; TNT; Uptake; Wheat